대학 수준의 온라인 학습환경에서 성별과 상호작용 방식에 따른 사회적 실재감 비교 연구 - 모수경(Mo, Sukyoung) (교양교육연구, 2021)
이 연구의 목적은 대학 수준의 온라인 학습공동체에서 학습자의 사회적 실재감을 탐구하여 학습자간 상호작용을 촉진하는 방안을 모색하기 위함이다. 연구 대상은 15주간 교양영어 교과목을 수강한317명의 학부생으로, 이들은 비동기식 상호작용 집단과 동기식 상호작용 집단으로 구분되었다. 이 연구는자료의 수집과 분석에 혼합연구방법(mixed-method approach)을 채택하였다. 탐구공동체(Community of Inquiry, CoI) 설문조사 도구의 사회적 실재감 문항을 반영한 설문조사 결과에 대하여 이원배치분산분석(Two-way ANOVA)과 독립표본 t-검정(independent samples t-test)을 시행하였다. 설문조사의개방형 질문과 표본집단 서면 인터뷰는 개방 코딩방식의 범주화 작업을 통하여 분석하였다. 분석 결과에따르면, 첫째, 성별에 따른 사회적 실재감은 유의미한 차이를 보이지 않았으며, 성별은 상호작용 방식과함께 작용할 때 사회적 실재감에 유의미한 차이를 보였다. 둘째, 상호작용 방식에 따른 사회적 실재감은통계적으로 유의미한 차이를 보였다. 즉, 상호작용이 자주 일어나고 양질의 상호작용이 일어나는 집단에서 학습자의 사회적 실재감이 더 높았던 것으로 나타났다. 이는 상호작용 방식의 맥락에서 사회적실재감을 고려해야 함을 시사한다. 셋째, 온라인 학습공동체에서 학습자의 유대감과 친밀감 형성은사회적 실재감을 발달하도록 돕는 중요한 요소였으며, 학습 참여에 대한 학습자들의 인식은 학습공동체내의 학습자-학습자 상호작용과 밀접한 관련이 있었다. 이 연구는 학습자의 사회적 실재감을 촉진하고학습자 간의 상호작용을 도모하기 위한 교수자의 역할에 대한 제언으로 마무리한다. This study seeks ways to promote S-S interaction by exploring students’ social presence in a college-level online learning community. The subjects of this study were 317 undergraduate students who attended a 15-week general English course, and they were divided into asynchronous and synchronous interaction groups. This study adopted a mixed-method approach for data collection and analysis. A two-way analysis of variance (ANOVA) and an independent samples t-test analyzed quantitative data from the questionnaire adapting the social presence items in the Community of Inquiry Survey Instrument. A categorization by open coding was performed on the open-ended items of the questionnaire and a written focus group interview. The results revealed that social presence by gender was not significantly different. However, there was a statistically significant difference in social presence when gender exchanged its effect with interaction means. Social presence by interaction means showed a statistically significant difference. Of the two, the group with frequent and good-quality interaction perceived higher social presence. The findings indicate social presence needs to be considered in the context of interaction means. The formation of a sense of bond and intimacy in the online learning community was crucial in developing their social presence. The students’ perception of participation was closely related to S-S interaction in the online learning community. This study concludes with a suggestion for instructors to facilitate students’ social presence and promote S-S interaction. KCI Citation Count: 6